Cyclooxygenase-1 and -2 expression in rheumatoid synovial tissues. Effects of interleukin-1 beta, phorbol ester, and corticosteroids. - Crofford, L J (1994)
High levels of immunoreactive cyclooxygenase (Cox; prostaglandin H synthase) are present in synovia from patients with rheumatoid arthritis (RA). We now show that the recently identified inducible isoform of Cox, Cox-2, is expressed in synovia from patients with RA. To further explore modulation of the Cox isoforms in RA synovial tissues, we examined the expression and modulation of Cox-1 and -2 in rheumatoid synovial explant cultures and cultured rheumatoid synovial fibroblast-like cells (synoviocytes). Immunoprecipitation of in vitro labeled proteins and Western blot analysis demonstrated the presence of both Cox-1 and -2 under basal conditions in freshly explanted rheumatoid synovial tissues. De novo synthesis of Cox-2 polypeptide was enhanced by IL-1 beta or PMA, and dramatically suppressed by dexamethasone (dex). Cox-1 expression, under the same conditions, showed only minor variation. Since mRNA for Cox-2 is highly unstable, we examined the regulation of Cox-2 transcripts in cultured rheumatoid synoviocytes. Under basal conditions both Cox-1 and -2 mRNAs were present at low levels, but Cox-2 mRNA was markedly increased by treatment with IL-1 beta or PMA. dex markedly suppressed the induction of Cox-2 mRNA. In sharp contrast, Cox-1 transcripts were not modulated by IL-1 beta or dex. These data suggest that modulation of Cox-2 expression by IL-1 beta and corticosteroids may be an important component of the inflammatory process in synovial tissues from patients with RA.